2014
DOI: 10.14207/ejsd.2014.v3n4p125
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Materialism and Consumer Ethics on Ecological Behavior: An Empirical Study

Abstract: World populations have increased day by day. Thus, production volume of companies have increased depend on increasing population. Besides, fashion and/or technology influence consumer's goods or services purchasing decision. Consequently, the type and the number of product produced have increased and natural resources both more are being used and depleted. At this point has come to the fore the consumer's environmental concern and ecological behavior and has gained importance. Studies about environmental conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Sustainable consumption is often associated with self-transcendence and “collective-oriented” values that advocate selflessness, harmony, concern about public welfare and connectedness with others (Pepper et al , 2009; Segal and Podoshen, 2013; Sevgili and Cesur, 2014). Some research evidence proposes a negative relationship between materialism and sustainable consumption, with materialism being found to have a negative impact on environmental concern, environmentally responsible behaviour, ecological behaviour and engagement in pro-environmental behaviour (see Kilbourne and Pickett, 2008; Bakırtaş et al , 2014; Bergman et al , 2014; Ku and Zaroff, 2014). In general, then, it can be said that materialism and conspicuous motives are considered to be obstacles for achieving sustainable consumption and a sustainable society.…”
Section: Reflections On the Relationship Between Sustainable And Conspicuous Consumptionmentioning
confidence: 99%
“…Sustainable consumption is often associated with self-transcendence and “collective-oriented” values that advocate selflessness, harmony, concern about public welfare and connectedness with others (Pepper et al , 2009; Segal and Podoshen, 2013; Sevgili and Cesur, 2014). Some research evidence proposes a negative relationship between materialism and sustainable consumption, with materialism being found to have a negative impact on environmental concern, environmentally responsible behaviour, ecological behaviour and engagement in pro-environmental behaviour (see Kilbourne and Pickett, 2008; Bakırtaş et al , 2014; Bergman et al , 2014; Ku and Zaroff, 2014). In general, then, it can be said that materialism and conspicuous motives are considered to be obstacles for achieving sustainable consumption and a sustainable society.…”
Section: Reflections On the Relationship Between Sustainable And Conspicuous Consumptionmentioning
confidence: 99%
“…4 Numerous studies have shown that higher levels of materialism are associated with less pro-environmental behavior. [5][6][7][8] In other words, materialistic lifestyles will aggravate environmental stress in the future. However, the pursuit of material enjoyment has become a universal social phenomenon.…”
Section: Introductionmentioning
confidence: 99%